Synthesis and Luminescent Properties of Red Phosphor Na1.8Zn2.1(MoO4)3Eu by Sol-Gel Method - Zhang, Jianfu; Zhang, Hui; Ran Geng, Ke; Ling Wang, Zhen (Asian Journal of Chemistry, 2014)
The red phosphor Na1.8Zn2.1(MoO4)3Eu was prepared by sol-gel method. The effects of doping concentration and firing temperature on the crystal structure and luminescent properties were investigated by X-ray powder diffraction, scanning electron microscope and fluorescence spectrum. The results indicated that the phosphor exhibited intense red photoluminescence at 610 nm when excited by the light of 464 nm, which was attributed to 5D0 ® 7F2 transition of Eu3+.